PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI PEMASANGAN BARU LISTRIK BERBASIS WEB BARCODE - Andri Suryadi; Asep Ahmad K; Sri Rahayu; Nina Herlina; Yola Yulianti (Institut Pendidikan Indonesia, 2019)
Abstract - The new electrical installation information system is an information system that hasbeen computerized by the system. in a new electrical installation system the admin enters the dataof the applicant who wants to pair the new electricity in his home automatically to the databaseand makes it easy for the admin to search for data in the future. If the system is not computerizedand only manually, the applicant's data will still be stacked in a file cabinet, so that when makingthe report it has difficulty in searching the applicant's data and has the risk of losing data. This isbecause it is not supported by the presence of storage media in the form of a database system formanagement of applicant data. Based on this, the new web barcode-based electrical installationinformation system can help the applicant in registering the electricity installation and become asystem of information delivery that can provide convenience in processing the applicant's data foradministrative staff, especially in processing and data storage applicant data.Keywords - Systems, Information, Installation of new electricityAbstrak - Sistem informasi pemasangan listrik baru merupakan sistem informasi yang tsudahterkomputerisasi sistemnya . dalam sebuah sistem pemasangan listrik baru admin menginputkan datapemohon yang ingin memasangkan listrik baru dirumahnya secara otomatis ke database dan memudahkanadmin dalam pencarian data dikemudian hari . Jika sistem nya belum terkomputerisasi dan hanya manual sajanantinya data pemohon masih ditumpuk dalam lemari arsip, sehingga pada saat pembuatan laporan memilikikesulitan dalam pencarian data pemohon dan memiliki resiko kehilangan data. Hal ini karena tidak didukungdengan adanya media penyimpanan berupa sistem database untuk manajemen data pemohon. Berdasarkan haltersebut maka dengan sistem informasi pemasangan listrik baru berbasis web barcode , ternyata dapatmembantu pemohon dalam mendaftar pemasangan listrik dan menjadi sistem penyampaian informasi yangdapat memberikan kemudahan dalam hal pengolahan data pemohon bagi pegawai bagian administrasi padakhususnya dalam melakukan pengolahan dan juga penyimpanan data-data pemohon.Kata Kunci : Sistem, Informasi, Pemasangan baru listrik